LEGAL CERTAINTY IN THE TRANSFER OF LAND RIGHTS THROUGH ELECTRONIC CERTIFICATES IN THE PRACTICE OF LAND DEED OFFICIALS (PPAT) - Markus Gunawan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The migration of Indonesian land administration from paper certificates to electronic certificates, initiated by Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 1 of 2021 and consolidated by Regulation No. 3 of 2023, is presented by the State as a guarantee of legal certainty. This study interrogates that claim at the point where it is actually tested: the office of the Land Deed Official (Pejabat Pembuat Akta Tanah, PPAT), through which every conveyance of registered land must pass. Using a normative juridical method with statutory, conceptual, and case approaches, the study examines whether the electronic certificate regime in fact delivers certainty in the transfer of land rights, and identifies the obstacles that arise in PPAT practice. The findings are threefold. First, electronic certificates strengthen what may be termed documentary and procedural certainty - integrity of the record, verifiability, and speed - but they do not and cannot alter the substantive character of Indonesian land registration, which remains a negative system with positive tendencies under Article 19 of the Basic Agrarian Law and Article 32(2) of Government Regulation No. 24 of 1997. Digitalisation improves the reliability of the register; it does not confer indefeasibility of title. Second, a structural normative tension persists between the electronic land regime and Article 5(4) of the Electronic Information and Transactions Law, which excludes instruments required by law to take the form of a notarial or official deed from the scope of electronic documents; the PPAT deed therefore remains a paper instrument executed in physical presence, while the certificate it operates upon has become electronic. Third, in practice the resulting hybrid produces friction: incomplete media conversion, dual-format certificates circulating simultaneously, uneven readiness of land offices and PPAT offices, unresolved allocation of liability for verification failures, and personal-data exposure under Law No. 27 of 2022. The study argues that legal certainty in electronic conveyancing depends less on the digital format of the certificate than on the coherence of the norms surrounding it, and proposes a targeted reform agenda comprising an explicit statutory basis for electronic PPAT deeds, a standardised electronic verification protocol with a defined evidentiary effect, a clear allocation of liability between the Land Office and the PPAT, and a transitional framework governing the coexistence of analogue and electronic certificates.